2013
DOI: 10.1002/ijc.28073
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent mutations of KRAS and PIK3CA affect the efficacy of NVP‐BEZ235, a dual PI3K/MTOR inhibitor, in regulating the PI3K/MTOR pathway in colorectal cancer

Abstract: Colorectal cancer (CRC) with mutational activation of KRAS is observed frequently. In addition, PIK3CA mutations commonly coexist with KRAS mutations and lead to additive activation of the PI3K/MTOR signaling pathway. Here, we investigated how CRC cells that harbor KRAS and PIK3CA mutations affect sensitivity to inhibition of PI3K/MTOR with NVP-BEZ235 (BEZ235). We selected CRC patient samples and assessed their mutational status. CRC patients with KRAS or PIK3CA mutations show activation of AKT and MTOR, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 47 publications
3
38
1
1
Order By: Relevance
“…Mutational activation of KRAS, when accompanied by a PIK3CA activating mutation, resulted in resistance to BEZ235 in colorectal carcinoma cells [80]. In T cell acute lymphoblastic leukemia cell lines, PI-103 caused upregulation of Notch1/c-Myc signaling, which led to an impaired cytotoxic response [81].…”
Section: Rapalogs and Combination Therapymentioning
confidence: 99%
“…Mutational activation of KRAS, when accompanied by a PIK3CA activating mutation, resulted in resistance to BEZ235 in colorectal carcinoma cells [80]. In T cell acute lymphoblastic leukemia cell lines, PI-103 caused upregulation of Notch1/c-Myc signaling, which led to an impaired cytotoxic response [81].…”
Section: Rapalogs and Combination Therapymentioning
confidence: 99%
“…Activating mutations in the KRAS gene result in resistance to treatment of colorectal cancer cell lines with BEZ235, a PI3K/mTOR inhibitor [133]. Furthermore, amplification of eIF4E or c-MYC confers resistance to treatment with the same inhibitor in tumor cell lines [134].…”
Section: Pi3k/mtor Inhibitorsmentioning
confidence: 99%
“…Preclinical models have indicated intrinsic resistance associated with simultaneous mutation of KRAS or BRAF in PIK3CA-mutated tumors, highlighting the need for combination strategies [16,17]. Similarly, the exonic location of PIK3CA mutations may influence response to PI3K pathway inhibition; for example, a recent analysis of multiple CRC cohorts suggested that mutations in PIK3CA exon 20, but not exon 9, are predictive of resistance to EGFR inhibition [18].…”
mentioning
confidence: 96%
“…Direct testing for PIK3CA mutation and PTEN expression in isolation may have limited predictive utility, with frequent co-occurrence of resistance KRAS or BRAF mutations [17]. Molecular predictive signatures, rather than individual biomarkers, may therefore be required, potentially comprising mutation, gene and protein expression.…”
mentioning
confidence: 98%